2005
DOI: 10.1179/016164105x18430
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and metal content in blood and cerebrospinal fluid of amyotrophic lateral sclerosis patients with and without a Cu, Zn-superoxide dismutase mutation

Abstract: Hydroxyl radical, ascorbate free radical, superoxide dismutase (SOD) activities, Cu,Zn-SOD protein, Mn-SOD protein, 8-hydroxy-2' -deoxyguanosine (8-OHdG) and metals were compared in red blood cells (RBC), plasma and/or cerebrospinal fluid (CSF) between patients with sporadic amyotrophic lateral sclerosis (SALS), familial ALS (FALS) showing the Leu126Ser mutation in the Cu, Zn-SOD gene and controls. In patients with FALS or SALS, concentrations of hydroxyl radical in blood and ascorbate free radical and 8-OHdG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 8 publications
1
72
1
1
Order By: Relevance
“…Markers for protein and lipid oxidation were detected in motor neurons, reactive astrocytes, and microglia or macrophages (Shibata et al 2001). Cerebrospinal fluid samples from ALS patients demonstrate increased levels of 8-OHdG (indicative of DNA oxidation), 4-hydroxynonenal (indicative of lipid peroxidation), ascorbate free radical, 3-nitrotyrosine levels and nitrated manganese superoxide dismutase (Smith et al 1998;Tohgi et al 1999;Aoyama et al 2000;Bogdanov et al 2000;Simpson et al 2004;Ihara et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Markers for protein and lipid oxidation were detected in motor neurons, reactive astrocytes, and microglia or macrophages (Shibata et al 2001). Cerebrospinal fluid samples from ALS patients demonstrate increased levels of 8-OHdG (indicative of DNA oxidation), 4-hydroxynonenal (indicative of lipid peroxidation), ascorbate free radical, 3-nitrotyrosine levels and nitrated manganese superoxide dismutase (Smith et al 1998;Tohgi et al 1999;Aoyama et al 2000;Bogdanov et al 2000;Simpson et al 2004;Ihara et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Elevated levels of 8-OHdG (205) and HNE (355) were observed in CSF samples from ALS patients. Transgenic mouse and cell culture models of ALS showed a similar pattern of oxidation that was confirmed by the findings of increased levels of oxidative damage to protein, lipid, and DNA observed in the human disease (15,145).…”
Section: G93amentioning
confidence: 99%
“…Before the discovery linking SOD1 and ALS, epidemiological studies on ALS suggested that exposure to metallic trace elements was a significant factor among many other environmental factors such as viruses, strenuous exercise, and excitotoxic chemicals that may have a role in ALS etiology (4 -6). Studies on exposure to and tissue accumulation of metallic elements in ALS patients show a correlative yet unspecified role for many metals including copper and zinc in SOD1-related ALS (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Over the years, a number of hypotheses relating metal toxicity to ALS have been proposed.…”
mentioning
confidence: 99%